2019
DOI: 10.1007/s00394-019-01916-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytosomal curcumin on anthropometric parameters, insulin resistance, cortisolemia and non-alcoholic fatty liver disease indices: a double-blind, placebo-controlled clinical trial

Abstract: Purpose Curcumin has shown to exert a positive impact on human glucose metabolism, even if its bioavailability is usually very low. The present study aimed to explore the effect of phosphatidylserine-and piperine-containing curcumin phytosomes on a large number of metabolic parameters related to insulin resistance, in the context of a randomized double-blind placebocontrolled trial involving 80 overweight subjects with suboptimal fasting plasma glucose. Methods Subjects were randomized to be treated with indis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 40 publications
3
125
1
3
Order By: Relevance
“…In the overall pooled estimate of eight trials (Chashmniam et al, ; Cicero et al, ; Jazayeri‐Tehrani et al, ; Mirhafez et al, ; Navekar et al, ; Panahi et al, ; Rahmani et al, ; Saadati et al, ) with 520 participants (a dose ranging from 70 to 3,000 mg/day), it was shown that curcumin supplementation was associated with a significant reduction in BMI (WMD = −0.34 kg/m 2 , 95% CI [−0.64, −0.04], p < .05) compared with the control group (Figure ). The heterogeneity among trials investigating the effect of curcumin supplementation on BMI was high ( I 2 = 63.2%, p < .01).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the overall pooled estimate of eight trials (Chashmniam et al, ; Cicero et al, ; Jazayeri‐Tehrani et al, ; Mirhafez et al, ; Navekar et al, ; Panahi et al, ; Rahmani et al, ; Saadati et al, ) with 520 participants (a dose ranging from 70 to 3,000 mg/day), it was shown that curcumin supplementation was associated with a significant reduction in BMI (WMD = −0.34 kg/m 2 , 95% CI [−0.64, −0.04], p < .05) compared with the control group (Figure ). The heterogeneity among trials investigating the effect of curcumin supplementation on BMI was high ( I 2 = 63.2%, p < .01).…”
Section: Resultsmentioning
confidence: 99%
“…The results from meta‐analysis of four trials (Cicero et al, ; Jazayeri‐Tehrani et al, ; Panahi et al, ; Saadati et al, ) with 301 participants (curcumin group = 153 and control group = 148) showed that daily supplementation of curcumin had a significant reducing effect on WC (WMD = −2.12 cm, 95% CI [−3.26, −0.98], p < .001) as compared with placebo using random‐effect model (Figure ). Nonlinear dose–response meta‐analysis showed a significant effect of supplementation dosage on WC ( p nonlinearity = .005, goodness of fit = 4.13; Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations